Quantification of pelvic floor muscle strength in female urinary incontinence: A systematic review and comparison of contemporary methodologies. Issue 1 (4th May 2017) - Deegan, Emily G.; Stothers, Lynn; Kavanagh, Alex; Macnab, Andrew J.
Abstract : Aims: There remains no gold standard for quantification of voluntary pelvic floor muscle (PFM) strength, despite international guidelines that recommend PFM assessment in females with urinary incontinence (UI). Methods currently reported for quantification of skeletal muscle strength across disciplines are systematically reviewed and their relevance for clinical and academic use related to the pelvic floor are described. Methods: A systematic review via Medline, PubMed, CINHAL, and the Cochrane database using key terms for pelvic floor anatomy and function were cross referenced with skeletal muscle strength quantification from 1946 to 2016. Full text peer‐reviewed articles in English having female subjects with incontinence were identified. Each study was analyzed for use of controls, type of methodology as direct or indirect measures, benefits, and limitations of the technique. Results: A total of 1586 articles were identified of which 50 met the inclusion criteria. Nine methodologies of determining PFM strength were described including: digital palpation, perineometer, dynamometry, EMG, vaginal cones, ultrasonography, magnetic resonance imaging, urine stream interruption test, and the Colpexin pull test. Thirty‐two percent lacked a control group. Conclusion: Technical refinements in both direct and indirect instrumentation for PFM strength measurement are allowing for sensitivity. However, the most common methods of quantification remain digital palpation and perineometry; techniques that pose limitations and yield subjective or indirect measures of muscular strength. Dynamometry has potential as an accurate and sensitive tool, but is limited by inability to assess PFM strength during dynamic movements.